Perancangan Mesin Hot Press Untuk Pengolahan Limbah Sampah Plastik Menjadi Produk Plastic Sheet - Simangunsong, Helfran; Hermanto, Tino; Purba, Tiochanra (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2024)
Plastic waste is a critical issue underlying the design of the hot press machine. This study aims to design a hot press machine capable of processing plastic waste into plastic sheet products and evaluate the safety and operational aspects of the machine. The method employed involves designing modelling using SolidWorks software and collecting data on the machine's design specifications. The results indicate that (1) the critical load capacity of the hollow steel frame reaches 4019.23 kN, (2) the spring pressure is 100,000 Pa, (3) the jack pressure is 5.3 MPa, (4) the electrical power consumption of the hot press machine is 2.22 kW, and (5) the electrical power for 10 cartridge heaters is 1,472.42 Watts. The mould pressure is 2.20 kN with a surface area of 4.16 cm², a plastic sheet thickness of 10 mm, and a 950 kg/m³ density. In conclusion, the machine frame dimensions are 600 mm x 600 mm x 1200 mm, utilizing 40 mm x 40 mm hollow steel profiles. Safety evaluations emphasize the importance of using personal protective equipment (PPE), adhering to operational procedures, and preparing for emergencies.